Physician’s and patient’s gender influence on suicide risk assessment: a cross-sectional study - Milène Barboteo; Aurélie M. Lasserre; Joseph Studer; Sebastien Brovelli; Carole Clair; Laurent Michaud (Cogent Psychology)
Background The association between patient and physician gender and suicide risk assessment is understudied, despite known differences in suicidal behaviors among genders.Aims To estimate the association between physicians’ sociodemographics and their rating of suicide risk and the need for hospitalization in men and women.Method In an anonymous online survey, physicians rated the suicide risk and the need for hospitalization of two clinical vignettes (one male and one female patient) and answered sociodemographic questions. Generalized estimating equations were used to estimate the associations between the vignettes’ gender and physician’s characteristics with the ratings of suicide risk and hospitalization needs.Results Of the 473 physicians who answered the survey, 407 were eligible for the study. Independently of other socio-demographics, (i) male physicians rated suicide risk and hospitalization need lower than their female counterparts, (ii) scores for female and male patients didn’t differ, and (iii) physicians rated higher hospitalization need for same-gender patients.Limitations We used a binary categorization for gender, which does not account for non-binary and other gender identities.Conclusion Physician gender impacts evaluations of suicide risk and the need for hospitalization. Future studies should explore how physician gender affects clinical practice and inform gender-sensitive medical training.